Biomineralized polypropylene/CaCO3 composite nonwoven meshes for oil/water separation. Issue 4 (18th September 2013) - Liao, Ke; Ye, Xiang‐Yu; Chen, Peng‐Cheng; Xu, Zhi‐Kang
ABSTRACT Polypropylene/calcium carbonate (CaCO3) composite nonwoven meshes were prepared on the basic principle of biomineralization by using a facile alternate soaking process (ASP) within 20 min. Negatively charged poly(acrylic acid) brushes, which can induce CaCO3 nucleation, were first tethered onto the fiber surface of polypropylene nonwoven meshes via UV‐induced graft polymerization. ASP procedure was followed to mineralize CaCO3 particles on the fiber surface and to form the composite nonwoven meshes. Fourier transform infrared spectroscopy/attenuated total reflectance, field emission scanning electron microscope, equipped X‐ray spectroscope, and X‐ray diffraction were used to characterize the prepared composite meshes. The mineral cover density increased with the ASP cycles, and it progressively increased for the relative content of calcite in the crystalline part of the mineral layer as well. Contact angle measurements indicate that the as‐prepared composite nonwoven meshes were endowed with superhydrophilicity and underwater superoleophobicity, thus they showed prominent application prospects in wastewater treatment and oil/water separation. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39897.